Relevance of Targeting Oxidative Stress, Inflammatory, and Pro-Resolution Mechanisms in the Prevention and Management of Postoperative Atrial Fibrillation - Abir Attia; Kalai Mangai Muthukumarasamy; Doa’a G. F. Al-U’Datt; Roddy Hiram (Antioxidants)
Atrial fibrillation (AF) is the most common cardiac arrhythmia. AF can lead to severe complications, including stroke, myocardial infarction, and sudden death. AF risk factors include pathological aging and conditions such as obesity, diabetes, and hypertension. Clinical data revealed that cardiothoracic and non-cardiothoracic surgeries are also important risk factors for AF. Post-operative AF (POAF) is associated with important public health costs caused by increased hospitalization, frequent emergency room visits, and enhanced healthcare utilization, which altogether lead to a low quality of life for the patients. Hence, POAF is a major clinical challenge, and there is an urgent need for the development of novel therapeutic strategies. Interestingly, evidence from clinical and fundamental research converges to identify cardiac oxidative stress and atrial inflammation as the common denominators of all AF risk factors. Unresolved inflammation is suspected to provoke cardiac fibrosis, which is an important contributor to cardiac arrhythmias and AF. Antioxidant, anti-inflammatory, and pro-resolution strategies may help to combat post-operative cardiac remodeling and POAF. This article aims to review the current scientific evidence supporting the role of inflammation in the pathogenesis of POAF and explore potential novel therapeutic strategies to prevent and mitigate inflammation in the management of AF.